2022
DOI: 10.1332/239868021x16316184865237
|View full text |Cite
|
Sign up to set email alerts
|

Beyond intimate partner relationships: utilising domestic homicide reviews to prevent adult family domestic homicide

Abstract: Increasing evidence documents domestic violence and abuse (DVA) and domestic homicide of adults killed by a relative in non-intimate partner relationships. Most literature focuses on intimate partner violence and homicide, yet non-intimate partner homicides form a substantial but neglected minority of domestic homicides. This article addresses this gap by presenting an analysis from 66 domestic homicide reviews (DHRs) in England and Wales where the victim and perpetrator were related, such as parent and adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 21 publications
(39 reference statements)
2
27
0
Order By: Relevance
“…This perhaps mirrors its exceptionalization and bounding in the policy documents. Finally, engaging with victim subjectivity and agency relies on how information is reported, but ironically some DHRs contain limited victim information (Bracewell et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This perhaps mirrors its exceptionalization and bounding in the policy documents. Finally, engaging with victim subjectivity and agency relies on how information is reported, but ironically some DHRs contain limited victim information (Bracewell et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…(Chantler et al, 2020: 491) A recent document analysis of DHRs concerning adult family homicide sought to provide a more detailed overview of methods, including quantitative and qualitative data extraction. It summarised the challenges encountered, noting absent information regarding socio-demographics of victims and perpetrators and -perversely given the aspiration that victims should be central to DHRs -that information about the victim is often lacking compared to the perpetrator (Bracewell et al, 2021).…”
Section: Methodology and Dhrsmentioning
confidence: 99%
“…Meanwhile, scholarship has largely focused on the secondary analysis of cases and associated recommendations (Sharp-Jeffs and Kelly, 2016;Home Office, 2016b). In other examples, DHRs have been used to explore the experience of specific cohorts, including older people or children (Bracewell et al, 2021;Benbow et al, 2019;Stanley et al, 2019); patterns in abusive relationships (Monckton Smith, 2020); particular forms of abuse (Todd et al, 2021); and system responses (Dheensa, 2020;SCIE, 2020).…”
Section: Utilising Dhrs For Research Purposesmentioning
confidence: 99%
“…Bows (2019) found that most deaths occurred in the victim’s home and that a sharp instrument was most frequently involved. A recent study by Bracewell et al (2021) identified “five interlinked precursors” in the perpetration of adult family homicide, namely, mental health and alcohol/substance misuse; criminality; childhood trauma (childhood abuse or death of a parent); “caring” relationships; and economic issues.…”
Section: What Is Known About Adult Family Violence and Homicide?mentioning
confidence: 99%